2020
DOI: 10.1021/acs.biomac.0c00897
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Functionalized Expanded Polytetrafluoroethylene Blood Vessel Grafts

Abstract: Cardiovascular diseases plague human health because of the lack of transplantable small-diameter blood vessel (SDBV) grafts. Although expanded polytetrafluoroethylene (ePTFE) has the potential to be used as a biocompatible material for SDBV grafts, long-term patency is still the biggest challenge. As discussed in this paper, by virtue of a novel material formulation and a new and benign alcohol/water lubricating agent, biofunctionalized ePTFE blood vessel grafts aimed at providing long-term patency were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…It has excellent biocompatibility and special microporous structure. It is used in wound dressings, heart valves, artificial blood vessels, cosmetic plastic surgery, and other fields which have been successfully applied; it is an ideal biological tissue replacement material [20][21][22][23]. In addition, studies on ePTFE in dural repair surgery revealed that ePTFE filling can significantly increase the success rate of surgery and effectively reduce the occurrence of complications such as syringomyelia.…”
Section: Introductionmentioning
confidence: 99%
“…It has excellent biocompatibility and special microporous structure. It is used in wound dressings, heart valves, artificial blood vessels, cosmetic plastic surgery, and other fields which have been successfully applied; it is an ideal biological tissue replacement material [20][21][22][23]. In addition, studies on ePTFE in dural repair surgery revealed that ePTFE filling can significantly increase the success rate of surgery and effectively reduce the occurrence of complications such as syringomyelia.…”
Section: Introductionmentioning
confidence: 99%
“…First, heparin, a universal anticoagulant, was immobilized on graft surfaces to reinforce the antithrombotic properties. [ 30–41 ] Heparin interacted with antithrombin III and enhanced inhibition of blood coagulant factors including factor Xa and thrombin, thereby avoiding blood coagulation. [ 42 ] Heparin in multiple layers can be immobilized on ε ‐polycaprolactone (PCL) graft surfaces by combining EDC/NHS coupling and layer‐by‐layer assembly, preventing long‐term thrombus formation.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%
“…One attractive stabilizing material is finely dispersed poly(tetrafluoroethylene) (PTFE), which consists of 0.1–0.5 μm granules 16 . The long lifetime of PTFE in aggressive environments makes it attractive for many innovative applications, including transplantation, 17 3D printing, 18 and environmental cleanup 19 …”
Section: Introductionmentioning
confidence: 99%